Mapping histories : essays presented to Ravinder Kumar - Kumar, Ravinder; Chandhoke, Neera (New Delhi : Tulika, 2000)
Contributed articles arranged in a broad chronological sequence on Indian historical studies on diverse topics.
Includes bibliographical references and index.
Keywords: India -- History